Comparison of several quick and simple methods in the investigation of microbial action on carbohydrates. - Ramos, A.; Díaz, Rosa Mª.; Callao, V. (Ars Pharmaceutica (Internet), 1967)
Comparativa a study is made of the advantages and disadvantages of different rapid methods applied to the investigation of the action of microorganisms on carbohydrates. The ideal procedure is the one which uses a culture medium with phenol red and paper disks impregnated with the sugar solution and bromophenol blue indicator at alkaline pH.